Analisis Sekuen Ekson 6-8 dari Gen Ferritin pada Tiga Varietas Padi (Oryza sativa l.) Asal Kecamatan Bantan, Bengkalis - Riau - ROSLIM, DEWI INDRIYANI; DEANESIA, DITA; , HERMAN (Jurnal Riau Biologia, 2016)
One of the obstacles encountered in Bengkalis agricultural is the high content of Fe in the soil. Fe ionscan cause toxicity in plants if it is accumulated in an amount exceeding the tolerable limit of the plant.This study was aimed to compare the nucleotide sequences of the ferritin2 gene in some rice genotypesfrom Riau commonly growing in tidal land in Bengkalis with Fe-overload-tolerant rice variety (Mahsuri)and national rice variety which was Fe- overload -sensitive (IR64). The research was conducted at theGenetic Laboratory, Faculty of Mathematical and Natural Sciences, Riau University from January to May2014. The methods included DNA isolation, PCR, electrophoresis, and sequencing. DNA sequence dataanalysis was performed by using the BLAST and MEGA programs. This study got Â± 750 bp DNAfragment of the ferritin2 gene which covering exons 6-8. Total number of SNPs obtained are as many as53 pieces and only found in introns and exons six. The farthest genetic distance was between Mahsuri andAmat Candu (0.171), followed by Sadani and Opium Amat (0.164). The shortest genetic distance wasbetween Korea and IR64 and also Sadani. Korea had the shortest distance to Nipponbare, otherwiseAmat Candu was the farthest distance from Nipponbare. Based on exons 6 to 8 sequence, Amat Canduwas classified as Fe- overload -sensitive rice variety, whereas Korea was a Fe- overload-tolerant ricevariety. Sadani was Fe-overload-moderate rice variety.Keywords : Riau, PCR, ferritin gene, Oryza sativaÂ¸ tidal land